PENYULUHAN PENANGANAN PASCA PANEN DAN PENGOLAHAN UBI JALAR UNGU BAGI SISWA SMK NEGERI 1 BAWEN KABUPATEN SEMARANG - Putri, Aldila Sagitaning; Larasati, Dewi; Sani, Elly Yuniarti (Fokus ABDIMAS, 2023)
SMK Negeri 1 Bawen is located in the Bawen District area which is located in Semarang Regency and has six Expertise Programs, namely the Agricultural Product Agribusiness Expertise Program, Plant Production Agribusiness, Livestock Production Agribusiness, Agricultural Mechanization, Culinary Planning and Tourism. graduates of SMK Negeri 1 Bawen are scattered throughout the archipelago and work in various sectors of the Business and Industry World. This community service activity aims to provide information to students at SMK Negeri 1 Bawen Semarang Regency about the importance of post-harvest handling of purple sweet potatoes and how to process them and provide skills on how to process purple sweet potatoes into purple rice and purple sweet potato ice cream. The partner's problem is that so far purple sweet potato has not been diversified, so this extension activity will increase knowledge about purple sweet potato processing. The activities carried out in the community service program entitled "Counseling on Post-harvest Handling and Processing of Purple Sweet Potatoes for Students of SMK Negeri 1 Bawen, Semarang Regency" are intended to broaden the knowledge of students of SMK Negeri 1 Bawen, so that it can become a provision for them to work and disseminated to the surrounding community. Therefore the targets in this community service activity are: a. Increased knowledge of students at SMK Negeri 1 Bawen about post-harvest handling of purple sweet potato by 98.7%, b. increased knowledge of students at SMK Negeri 1 Bawen in processing purple sweet potatoes into purple rice and purple sweet potato ice cream as much as 88.93%, c. increasing the skills of students in processing purple sweet potatoes into purple rice and purple sweet potato ice cream by 93.24%. The solution is that partners experience an increased understanding of how to process purple sweet potatoes into products that are rich in nutritional value such as purple rice and purple sweet potato ice cream. Keywords: Post harvest, processing, purple sweet potato, purple rice, ice cream